Analisis FEM Dari Suhu HAZ Dengan Pemodelan Sumber Panas Pada Proses Butt-Joint Menggunakan MSC Marc Mentat - Rokki Manurung; Septiani Silitonga; Yohanes Hutahaean; Charles S.P Manurung; Parulian Siagian; Richard A M Napitupulu (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2020)
The success of the welding process is the occurrence of good and strong welding joints that are inseparable from the influence of the heat source. The problem that often occurs when welding is a distortion that can trigger the initial formation of cracks. By predicting the level of welding distortion beforehand, engineers can also reduce the amount of rework by reverse design and distortion margins. That is why with current technological developments it is possible to carry out simulations based on analytical solutions that are implemented through the use of software, where in this study the authors sought to model the temperature of the HAZ region in the Butt Joint process using MSC Marc Mentat. The simulation results show that the heat source is very determining the occurrence of distortion and pressure on the surface. This is caused by the phenomenon of melting and shrinkage that occurs in a short time.